2020
DOI: 10.2166/wst.2020.176
|View full text |Cite
|
Sign up to set email alerts
|

Electro-activated persulfate oxidation of malachite green by boron-doped diamond (BDD) anode: effect of degradation process parameters

Abstract: In this paper, boron-doped diamond (BDD) electro-activated persulfate was studied to decompose malachite green (MG). The degradation results indicate that the decolorization performance of MG for the BDD electro-activated persulfate (BDD-EAP) system is 3.37 times that of BDD electrochemical oxidation (BDD-EO) system, and BDD-EAP system also exhibited an enhanced total organic content (TOC) removal (2.2 times) compared with BDD-EO system. Besides, the degradation parameters such as persulfate concentration, cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…78-2500) . The diffraction peaks located at 44 and 75.5° were indexed to crystal planes (111) and (220), respectively, indicating that the (111) surface is the most exposed surface for the BDD film anode . In addition, Raman spectra reflect the carbon composition and doping degree of the BDD anode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…78-2500) . The diffraction peaks located at 44 and 75.5° were indexed to crystal planes (111) and (220), respectively, indicating that the (111) surface is the most exposed surface for the BDD film anode . In addition, Raman spectra reflect the carbon composition and doping degree of the BDD anode.…”
Section: Resultsmentioning
confidence: 99%
“…30 The diffraction peaks located at 44 and 75.5°were indexed to crystal planes ( 111) and ( 220), respectively, indicating that the (111) surface is the most exposed surface for the BDD film anode. 31 In addition, Raman spectra reflect the carbon composition and doping degree of the BDD anode. As shown in Figure S2b, the peaks of 501 and 1222 cm −1 reflect the phonon scattering due to the change of diamond structure by boron doping.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In contrast, in many cases, pollutant oxidation is promoted under acidic pH conditions. ,, For example, Fernandes et al demonstrated that EE/O for the treatment of concentrated sanitary landfill leachate by AO is lower at pH 2.98 than that at pH 8.2 (No. 11 in Table ).…”
Section: Performance Evaluation Of Eopsmentioning
confidence: 99%
“…However, the optimal voltage value was 5 V because the continued increase in voltage would cause more secondary reactions. 45 …”
Section: Degradation Experimentsmentioning
confidence: 99%